Spiritual Health Status and its Relationship with Demographic Characteristics of Students of Mashhad University of Medical Science - Alireza Jafari; Mohammad Vahedian-Shahroodi (Hamadan University of Medical Sciences, 2019)
Aims: Spiritual health is one of the important aspects of health, which forms an important part of human life. The aim of this study was to determine the status of spiritual health and its relationship with demographic characteristics in students of Mashhad University of Medical Science. Instruments & Methods: This cross-sectional descriptive-analytical study was conducted on 256 students of Mashhad University of Medical Science in 2018. The subjects were selected by available sampling method. Data were collected using demographic questionnaire and Ellison and Paloutzian's Spiritual Wellbeing Scale (SWBS). Data were analyzed by SPSS 24 software using Mann-Whitney, Kruskal-Wallis, and Spearman's correlation tests. Findings: 84.0% of students (n=215) had moderate spiritual well-being. There was a significant relationship between gender with religious health dimension (p=0.002) and spiritual health score (p= 0.014). There was a significant relationship between the student's job status and grade and field of study with dimensions of religious health, existential health, and spiritual health score (p<0.01). There was a significant correlation between religious health, and existential health with spiritual health (p<0.001). Conclusion: Only a few students have a high level of spiritual health, and the majority of subjects have a moderate level of spiritual health. There is a relationship between gender and grade and field of study with their level of spiritual health.